Do the clinical outcomes of Covid-19 differ in pregnancy? - Aygün, Elif Ganime; Karabuk, Emine; Dilek, Talat Umut Kutlu (Journal of Surgery and Medicine, 2020)
In this brief review, we aimed to assess Covid-19 infection from a different aspect and emphasize the advantages of patients during pregnancy. Therefore, the course of Covid-19 infection and chronic diseases during pregnancy were evaluated. The disease seems to have a positive effect on fetomaternal circulation during pregnancy. Our hypothesis on this matter is that the regulation of the host immune system which occurs due to pregnancy may reduce the cytokine storm and multiple organ failure-related mortality in Covid-19 infected pregnant women.